Factors affecting oral health habits among children with cerebral palsy: Pilot study - (:unkn) unknown (WILEY, 2007)
Background: The aim of the present study was to investigate the factors affecting the oral health habits of children with spastic-type cerebral palsy (CP). Methods: A total of 35 children with CP and their mothers were randomly selected for this cross-sectional study. Data regarding their sociodemographic characteristics and their oral health habits were collected during face-to-face interviews. Results: Logistic regression analysis indicated that mothers' irregular brushing habits were a risk factor for their children's lack of regular brushing habits (odds ratio: 6.4, P = 0.048). Additionally, a significant association was observed between the mother's length of time between dental visits and the length of time between children's dental visits (R-2 = 0.11, P = 0.046). Conclusion: Mothers' oral health habits, including brushing habits and frequency of dental visits, are important factors in promoting healthy and beneficial oral health habits in children with CP in Turkey.
Keywords: cerebral palsy; oral health habits; EPIDEMIOLOGY